The Effectiveness of Using Social Media Facebook to Enhance EFL Students' Writing Skill - Hadiantoro, Hayus (Universitas Negeri Surabaya, 2022)
Online class has now become a primary way for teachers and students tohaveprogress in their education especially since the pandemic outbreak in 2020. Building a fun class is now becoming a challenge for teachers while teaching online. Social media has potential to be a good platform to build existing knowledge before the class starts. Most students arealsosocial media users. Social media has potential in English class to build the existing knowledge for students.The study uses true experimental design with quantitative approach and questionnaire as the instrument. The datathat were collected from 24 students at 11th grade in one of the senior high school in Surabaya shows that social media Facebook improves student’s writing skills. Students that using social media Facebook are tended to have improvement in writing.It improves students’ writing skill in vocabulary, content, grammar, mechanic, and organization.Studentsalsodeveloped knowledge from anothersocial media user.However, there still needed to do further research in order to find the details about the factorsthat affect the improvement.